2019
DOI: 10.12659/ajcr.917193
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Fasciitis/Myositis Involving the Facial Muscles Including the Masseter Muscle: A Rare Cause of Trismus

Abstract: Patient: Male, 50Final Diagnosis: Proliferative fasciitis/myositisSymptoms: Facial swelling • fever • trismusMedication: —Clinical Procedure: BiopsySpecialty: PathologyObjective:Rare diseaseBackground:Proliferative fasciitis/myositis is a benign disease that can be treated conservatively. However, some patients are mistakenly treated surgically because of a misdiagnosis of the condition as a malignant tumor.Case Report:A 50-year-old Japanese man developed swelling in his left cheek 12 days before admission; he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The general medicine department of this hospital manages the first-touch practice of outpatients without a reference from their primary doctors, in addition to treating both in-and outpatients with common diseases, fevers of unknown origin, diseases that are difficult to correctly diagnose, and complicated pathological situations requiring intensive care. [4][5][6][7] In this study, patients suspected of having, or diagnosed with IE before admission would, in principle, be seen by the endocarditis team of the department of cardiology and cardiovascular surgery. In comparison, patients with non-specific symptoms and signs such as fever of unknown origin, consciousness disorder, paralysis, or rash, who were not suspected of having, or were not diagnosed with IE prior to referral, would initially be seen by the department of general medicine, emergency medicine, neurology, or dermatology or whatever department seemed appropriate.…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The general medicine department of this hospital manages the first-touch practice of outpatients without a reference from their primary doctors, in addition to treating both in-and outpatients with common diseases, fevers of unknown origin, diseases that are difficult to correctly diagnose, and complicated pathological situations requiring intensive care. [4][5][6][7] In this study, patients suspected of having, or diagnosed with IE before admission would, in principle, be seen by the endocarditis team of the department of cardiology and cardiovascular surgery. In comparison, patients with non-specific symptoms and signs such as fever of unknown origin, consciousness disorder, paralysis, or rash, who were not suspected of having, or were not diagnosed with IE prior to referral, would initially be seen by the department of general medicine, emergency medicine, neurology, or dermatology or whatever department seemed appropriate.…”
Section: Settingmentioning
confidence: 99%
“…3 Among these departments, the general medicine departments, especially at university hospitals in Japan, which are often in charge of diagnosing diagnostically challenging diseases, including fevers of unknown origin, are likely to see patients with IE. [4][5][6][7] Our previous research showed that the general medicine department of Saga University Hospital in Japan diagnosed and treated the third-highest number of inpatients with IE after the departments of cardiology and cardiovascular surgery. 4 The department of cardiovascular surgery plays a clearly delineated role in treating IE in terms of when and how to operate and how to manage patients after surgery.…”
Section: Introductionmentioning
confidence: 99%